Analisis fitur pembayaran Shopee PayLater dalam sudut pandang ekonomi Islam - Daroini, Maiya Hasanatud (Maliki Interdisciplinary Journal, 2024)
Shopee PayLater is a feature that allows users to shop now and pay later, with options for payment within one month without interest or with installment payments with interest. Although this feature offers convenience, from an Islamic economic perspective, Shopee PayLater is controversial because it contains elements of riba, which is prohibited in Islam. Riba occurs when there is an obligatory addition to the repayment of a loan, either in the form of interest on installments or late payment penalties. In the qardh or loan contract according to Islam, any stipulated addition in the agreement is considered riba and is haram. Therefore, although Shopee PayLater facilitates transactions and has a clear agreement, the interest and late payment penalties make it inconsistent with sharia principles.